Slope Stability Assessment of The Garin Majjed Archeological Village Area, East of Yemen (Thamar University Journal of Natural & Applied Sciences, 2023)
The stability assessment of sedimentary rock slopes of the area surround Garin Majjed archeological village which lay on cuesta shape hill in Wadi Dawa’an - East of Yemen was carried out. All important factors affecting slope stability in the area such as differential weathering, rainfall and runoff, sewage, discontinuities trends and inclinations, slope face orientation, and mechanical properties of rocks and joints filling materials were evaluated. Direct shear test of joints filling materials showed that the friction angle (Φ) values range between 11˚ and 31˚ and cohesion (C) Values between 0.00 and 0.5 MPa. The compressive strength (cσ) values of the nodular limestone rocks is 66 MPa and for shaley marly sandstone it is 12 MPa. It was found that rock fall is the main mode of failure in the area, while secondary toppling and/ or plane sliding are probable to occur. Some remedial measures are proposed to protect the slopes like erect well seal drainage path, supporting the toe of the dip slope and the overhanging parts, as well as grouting of joints by convenient filling material.